2013
DOI: 10.1093/ndt/gft092
|View full text |Cite
|
Sign up to set email alerts
|

Vegetarian low-protein diets supplemented with keto analogues: a niche for the few or an option for many?

Abstract: Our data suggest a wider offer of LPD-KA to patients with severe and progressive CKD. The promising results in terms of mortality and progression need confirmation with different study designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 39 publications
3
56
0
Order By: Relevance
“…18,21,23 Less than one half of our patients fulfilling the selection criteria accepted to potentially follow a vegetarian diet, and only 14% proved compliant during the run-in phase and could be, therefore, randomized, a proportion that is higher than that recently reported by Piccoli et al 27 (1.5%). Compliance to LPDs could also be a problem.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…18,21,23 Less than one half of our patients fulfilling the selection criteria accepted to potentially follow a vegetarian diet, and only 14% proved compliant during the run-in phase and could be, therefore, randomized, a proportion that is higher than that recently reported by Piccoli et al 27 (1.5%). Compliance to LPDs could also be a problem.…”
Section: Discussionmentioning
confidence: 54%
“…Only 3% of our patients, equally distributed in the study arms, discontinued the diet, but those continuing the study showed excellent compliance to both protein and energy intake. This could be a center effect, because in other reports, 16% of patients chose to discontinue the KD diet, 27 and the compliance to an even less protein-restricted diet (0.55 g/kg per day) was only 27% and inversely related to the severity of protein restriction. 17 Nevertheless, our experience suggests that appropriate selection of patients, intensive counseling, and close monitoring could improve compliance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In many developing countries, the use of vegetarian diets along with keto acids has been shown to delay progression as well. [28][29][30][31][32][33] The switch to emphasizing higher protein ($1.0 g/kg/day) intake starts when the patient is in kidney failure and undergoing maintenance dialysis therapy. 34 Protein-energy wasting and chronic inflammation associated with malnutrition are often associated with hypoalbuminemia.…”
Section: Emphasis On Serum Albumin and Dietary Protein Qualitymentioning
confidence: 99%
“…Our diet for nonpregnant patients is vegan, with a protein intake of 0.6 g/kg per day (ideal weight), one to three free meals per week, and keto acid supplementation of 1 pill/8-10 kg ideal BW (IBW) (31,40).…”
Section: Low-protein Dietmentioning
confidence: 99%